Gram Positive Bacteria and Gram Negatives of clinical interest isolated in cell phones of medicine students in a peruvian university, 2019 - Díaz-Tello, José (2021)
The objective of this research is to characterize Gram Positive and Gram-Negative bacteria of clinical interest isolated from mobile phones, and to determine the substances used in their disinfection and cleaning frequency, in third year medical students of the Federico Villarreal University. 50 cell phones of the students were prospectively examined, the sample was taken with sterile swab from the surface of the mobile, it was cultivated in Blood Agar and in Mac Cokeny Agar. Identification was made at the genus and species level by manual conventional methodology. The bacterial phenotype is made up of Gram-Positive Bacteria of the genus Staphylococcus, which 29 strains are Staphylococcus coagulase negative (93.55%) and 2 Staphylococcus aureus strains (6.35%), the same as for 09 strains of Gram-Negative Bacteria within these we have 06 strains (66.67%) of Alcaligenes Sp, 02 strains (22.32%) and 01 strain (11.11%) of Escherichia coli. It was also observed that the phones of the males were isolated the highest number of bacteria, the disinfection and cleaning of mobile phones is done more per week and fortnight, mostly liquid alcohol - toilet paper, gel alcohol - toilet paper is used and toilet paper alone. This research concludes that the bacteria that are most isolated from the students' cell phones are: Stahyalococcus Coagulasa Negativo and Alcaligenes Sp, Males have more contaminated their devices, the most common cleaning and disinfection is carried out with liquid alcohol - toilet paper and is mostly done weekly.